2017
DOI: 10.15311/1441.309573
|View full text |Cite
|
Sign up to set email alerts
|

Effect of luting space and cements on retention of implant supported crowns fabricated by laser sintering

Abstract: ÖZLazer sinterize yoluyla üretilen implant destekli kronların tutuculuklarında siman aralığının ve simanların etkisi Amaç: Bu çalışmanın amacı iki farklı siman aralığı ile yapılan implant destekli kronlar için kullanılan beş farklı simanın tutuculuk mukavemetini değerlendirmektir. Gereç ve Yöntemler:Standart titanyum dayanaklar dijital bir 3D lazer tarayıcı aracılığıyla tarandı. 100 standart metal alt yapı bir CAD/CAM sistem aracılığıyla iki farklı siman aralığı değerinde (20 ve 40 µm) tasarlandı. Alt yapılar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Deepthi et al found that non-eugenol zinc oxide cement had the least retention compared to zinc phosphate cement and glass ionomer cement and stated that non-eugenol zinc oxide cement may not be suitable for luting single-unit implant-supported restorations [ 15 ]. Özyılmaz et al assessed the retention strength of various types of cements - Poly F (PF), GC FujiCEM (GCF), Rely X (RX) - and concluded that there was no considerable variation observed between RX and MCS and retention improved with increasing the cement gap from 20 to 40 µm [ 16 ]. Ahmed et al assessed the retention values and marginal adaptation of implant-supported metal copings using different luting agents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Deepthi et al found that non-eugenol zinc oxide cement had the least retention compared to zinc phosphate cement and glass ionomer cement and stated that non-eugenol zinc oxide cement may not be suitable for luting single-unit implant-supported restorations [ 15 ]. Özyılmaz et al assessed the retention strength of various types of cements - Poly F (PF), GC FujiCEM (GCF), Rely X (RX) - and concluded that there was no considerable variation observed between RX and MCS and retention improved with increasing the cement gap from 20 to 40 µm [ 16 ]. Ahmed et al assessed the retention values and marginal adaptation of implant-supported metal copings using different luting agents.…”
Section: Discussionmentioning
confidence: 99%
“…The present study found that non-eugenol temporary resin implant luting cement had the lowest retention value among the tested cements and the restoration can be removed easily due to its unique elasticity; hence it helps in easy retrievability of the prosthesis in cases of future failure. However, several other studies have stated that resin cements are useful for the cementation of single-implant prostheses for better retention [ 16 ]. The clinician should exercise great caution in the choice of cement as there is a high risk of component loosening based on the findings of the current study.…”
Section: Discussionmentioning
confidence: 99%
“…Mehl et al 29) investigated the effect of cement thickness on retention of 96 implantretained CAD/CAM crowns and found significant reduction in crown retention when cement space was increased from 15 to 50 μm. Contrarily, Özyılmaz et al 30) demonstrated a significant increase in retention of laser-sintered metal copings cemented on dental implant abutments when the cement space was increased from 20 to 40 μm. Meanwhile, CAD/CAM zirconia crowns with cement space of 80 μm had significantly higher retention compared with crowns with cement space of 100 and 120 μm 31) .…”
Section: Introductionmentioning
confidence: 99%